Single image reconstruction in active dynamic thermography : a novel approach - Saxena, Ashish (2019)
In the present study, a novel single thermal image reconstruction method, from the transient image series in active dynamic thermography (ADT), is proposed. ADT is performed with an external stimulation in the form of cooling, over the forearm skin tissue of a human subject, and the resulting transient images (due to thermal recovery) are captured using a non-contact Infrared (IR) thermal camera. A unique tissue activity ratio (), the ratio of thermal recovery rate to excitation rate is calculated at each pixel, and hence, a single thermal image (called image) is reconstructed. Using a conventional single image reconstruction method in ADT called Tau (τ) image method, a comparative study is performed, which reveals that the blood vessel contrast produced by the image is at least 1.3 times higher than the equivalent τ image. Further, using this image, the diameter of the blood vessel is calculated, and the values are compared with the τ image and the earlier reported thermography results on the same subjects, which reveals that the reconstructed image is an equivalent qualitative and quantitative representation of transient sequence images. The method devised can further be implemented for medical ADT procedures.